Bullying Prevalence in Students With Autism Spectrum Disorder*. Issue 2 (7th August 2017) - Campbell, Marilyn; Hwang, Yoon-Suk; Whiteford, Chrystal; Dillon-Wallace, Julie; Ashburner, Jill; Saggers, Beth; Carrington, Suzanne
Abstract : All forms of bullying, physical, verbal, social, and cyber, are prevalent among youth worldwide. An especially vulnerable population for involvement in bullying is students with an autism spectrum disorder (ASD). Although there are some studies that have investigated bullying in these students, many of these are beset by methodological issues. We surveyed 104 students with ASD on their bullying experiences in all 4 forms of bullying and examined their roles as victim, perpetrator, and bully-victim, comparing them with a group of typically developing students matched for age and gender. It was found that students with ASD reported significantly more traditional victimisation (physical, verbal, and social) than their typically developing peers. Cyberbullying victimisation was similar for the 2 groups. There were no differences between the groups on traditional bullying perpetration; however, typically developing students reported more cyberbullying perpetration behaviours. Implications for prevention and intervention are discussed.